Cultural landscape as a category of monuments and its specificity - Klupsz, Lidia (Protection of Cultural Heritage, 2016)
Cultural landscape is the most recently established category of historic sites. It has been functioning in Poland since 1990 and was mentioned for the first time in UNESCO documents in 1992. Its dual structure distinguishes it from other typology groups. As per the definition provided in the act of law, cultural landscape is an area shaped by natural factors and human activities. This field covers not only natural elements but also products of civilization. Clear and unambiguous criteria for classifying cultural landscapes according to the results of their valorisation have not been implemented into historical preservation yet. This results in difficulties in preserving and protecting cultural landscapes in Poland. Under the provisions of the European Landscape Convention, Polish government is obliged to take actions aimed at assessing landscape values. Therefore, there is a chance to resolve the stalemate.